Genomics and advances towards precision medicine for head and neck squamous cell carcinoma. Issue 5 (22nd August 2017) - Van Waes, Carter; Musbahi, Omar
Abstract : Objective: To provide a review of emerging knowledge from genomics and related basic science, preclinical, and clinical precision medicine studies in head and neck squamous cell carcinoma (HNSCC). Data Sources: The Cancer Genome Atlas Network (TCGA) publications, PubMed‐based literature review, and ClinicalTrials.gov. Review Methods: TCGA publications, PubMed, and ClinicalTrials.gov were queried for genomics and related basic science, preclinical, and developmental clinical precision medicine studies in HNSCC. Results: TCGA reported comprehensive genomic analyses of 279 HNSCC, defining the landscape and frequency of chromosomal copy number alterations, mutations, and expressed genes that contribute to pathogenesis, prognosis, and resistance to therapy. This provides a road map for basic science and preclinical studies to identify key pathways in cancer and cells of the tumor microenvironment affected by these alterations, and candidate targets for new small molecule and biologic therapies. Conclusion: Recurrent chromosomal abnormalities, mutations, and expression of genes affecting HNSCC subsets are associated with differences in prognosis, and define molecules, pathways, and deregulated immune responses as candidates for therapy. Activity of molecularly targeted agents appears to be enhanced by rational combinations of these agents and standard therapies targeting the complex alterations that affect multiple pathways and mechanisms in HNSCC. Level of Evidence: NA.